Common explosives (TNT, RDX, HMX) and their fate in the environment: Emphasizing bioremediation. (October 2017) - Chatterjee, Soumya; Deb, Utsab; Datta, Sibnarayan; Walther, Clemens; Gupta, Dharmendra K.
Abstract: Explosive materials are energetic substances, when released into the environment, contaminate by posing toxic hazards to environment and biota. Throughout the world, soils are contaminated by such contaminants either due to manufacturing operations, military activities, conflicts of different levels, open burning/open detonation (OB/OD), dumping of munitions etc. Among different forms of chemical explosives, 2, 4, 6-trinitrotoluene (TNT), hexahydro-1, 3, 5-trinitro-1, 3, 5-triazine (RDX), and octahydro-1, 3, 5, 7-tetranitro- 1, 3, 5, 7-tetrazocine (HMX) are most common. These explosives are highly toxic as USEPA has recommended restrictions for lifetime contact through drinking water. Although, there are several utilitarian aspects in anthropogenic activities, however, effective remediation of explosives is very important. This review article emphasizes the details of appropriate practices to ameliorate the contamination. Critical evaluation has also been made to encompass the recent knowledge and advancement about bioremediation and phytoremediation of explosives (especially TNT, RDX and HMX) along with the molecular mechanisms of biodegradation. Highlights: Toxicity and environmental concern of explosives. Interaction of explosives with soil and water. Abiotic methods for remediation of explosive. Recent knowledge about bioremediation and phytoremediation of explosives (especially TNT, RDX and HMX). Molecular aspects of biodegradation and application of transgenic plants.